Ionized Calcium Binding Adaptor Molecule 1 (IBA1): A Novel, Highly Sensitive, and Specific Marker for Histiocytic, Dendritic, and Monocytic Neoplasms. Issue 1 (14th February 2021) - Zhang, Xiaoming; Wang, Li-Ping; Ziober, Amy; Zhang, Paul J; Bagg, Adam
Abstract: Objectives: Ionized calcium binding adaptor molecule 1 (IBA1), a marker of microglia/macrophages, has not been investigated in human hematopathologic contexts. We evaluated its expression in mature and immature neoplasms of monocytic/histiocytic and dendritic cell (DC) origin. Methods: Immunohistochemistry for IBA1, CD14, CD68, and CD163 was performed on a total of 114 cases, including a spectrum of monocytic/histiocytic and DC neoplasms (20 tissue based and 59 bone marrow based) and several nonhistiocytic/monocytic/DC neoplasms as control groups (15 tissue based and 20 bone marrow based). Results: IBA1 expression was observed in all types of mature tissue-based histiocytic/DC neoplasms (20/20) but not in the corresponding control group (0/15). In bone marrow–based cases, IBA1 was expressed in most acute myeloid leukemias (AMLs) with monocytic differentiation (48/53), both blastic plasmacytoid dendritic cell neoplasms (2/2), and all chronic myelomonocytic leukemias (4/4), while it was positive in only one nonmonocytic AML (1/15) and none of the acute lymphoblastic leukemias (0/5). Collectively, IBA1 showed much higher sensitivity and specificity (93.7%, 97.1%) compared with CD14 (65.4%, 88.2%), CD68 (74.4%, 74.2%), and CD163 (52.6%, 90.6%). Conclusions: IBA1 is a novel, highly sensitive, and specific marker for diagnosing neoplasms of monocytic/histiocytic and DC origin.